Efeitos do enxofre e do boro e da inoculação em alfafa (Medicago sativa L.) - Malavolta, E.; Coury, T.; Galli, F.; Silva, J. Gomes da (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1952)
This paper deals with the results of a pot and plot experiment which was carried out to determine the influence of sulphur and boron and the effect seed inoculation with Rhizobium meliloti in the yield of alfafa. Sulphur was applied as flower of sulphur at the rates of 1,000 and 2,000 kg por hectare; boron was employed in the proportion of 15 kg of borax per hectare; both sulphur and boron were distributed broadcast before planting; the experimental design chosen for the field trial was a latin square of 6 x 6 with the following treatments: Number Treatment 1 Control 2 One dosis S + inoculation 3 Two dosis S +inoculation 4 One dosis S + B + inoculation 5 B + inoculation 6 inoculation The crop supplied four cuttings in an eleven months period. The pot experiment nearly confirmed the plot one. The following conclusions can be drawn: 1. The classification of treatments in a decrescent order was: l.o - two doses S + inoculation; 2.o - one dosis S +inoculation, S + B + inoculation, and B + inoculation (these treatmente were not statistically different); 3.o - control; 4.o - inoculation; 2 The vield due to the treatment two dosis S + inoculation was 22 per cent higher than the control one, a fact that suggests that the S supply in the soil studied ("terra roxa misturada") is not sufficient for the total requirements of alfafa; 3. From an economical point of view the best treatment was: one dosis B + inoculation which permits a net gain of Cr 12.527,30 per hectare per year; 4. Based on the mentioned results we recommend in soils of same type the following fertilization for alfafa. 5 tons limestone/hectare 300 kg serranafosfato and 600 kg hiperfosfato/ha 300 kg muriate of potash/ha 15 kg borax/ha and a medium organic manuring if the soil is very poor in organic matter.